APC licensing and CD4+T cell help in liver-stage malaria - Crispe, Ian N. (Frontiers in Microbiology, 2014)
Malaria parasites spend a critical phase of their life cycle inside hepatocytes, in an environment with complex and distinctive immunological features. Here I will discuss how the immunological features of the liver and the adaptations of malaria parasites interact, resulting in defective CD8+ T cell immunity. These processes are explored with a focus on the mechanism by which CD4+ T cells deliver help to CD8+ T cells, and specifically through their interaction with antigen-presenting cells, resulting in “licensing” of the antigen-presenting cell and enhanced capacity to optimally activate CD8+ T cells. Synthesis of the available evidence supports a model in which the parasite-mediated manipulation of programmed cell death in infected hepatocytes impairs the capacity of the liver’s immune system to successfully license antigen-presenting cells and fully activate T cell immunity.